Synthesis and Secretion of γ-Globulin by Lymph Node Cells, VIII. Order of Synthesis of the Interchain Disulfide Linkages of Immunoglobulins - Sutherland, Earl W. (1970)
Murine myeloma cells (ADJ-PC-5), incubated in vitro with (3)H-leucine, secrete (3)H-immunoglobulin G as a single molecular species as judged by the migration characteristics of the labeled product on sodium dodecyl sulfateacrylamide gel electrophoresis. However, the fact that some of the interchain disulfide linkages of intracellular immunoglobulins had not been acquired permitted the identification of the following intracellular species: LHHL (identical to immunoglobulin G), HHL, HH, and L (H and L refer to heavy and light polypeptide chains, respectively). Although HH and HHL were readily observed, radioactivity was not detected in the region of the gel where HL would be expected. The time course for the appearance of the intermediates indicates that in these cells the first interchain disulfide bond to be formed occurs between heavy chains. In contrast, the interchain disulfide bonds of immunoglobulins derived from rabbit lymph node cells were acquired in a different order. The principal intracellular species observed were LHHL and HL, whereas HHL and HH were not detectable. These findings indicate that in this species the first interchain disulfide bond to be formed is that between the heavy and light chains of immunoglobulin G.